The effectiveness of the learning service management strategy for students with autism in an inclusive elementary school - Nuraeni, Rani; Hidayat, Syarip; Mulyadi, Sima (Indonesian Journal of Primary Education, 2025)
This study aimed to determine the effectiveness of a learning service management strategy for children with autism in an inclusive elementary school. This study employed a case study as its research methodology, collecting data through interviews, observation, and documentation. The study results suggest that Muhammadiyah Private Elementary School effectively manages its services by implementing a curriculum that is modified or tailored to the specific needs of children with special needs. Additionally, the school conducted assessments to inform the planning of learning activities for students with autism. When creating Individualized Learning Plans, teachers employed various learning methods to accommodate students classified as having special needs. Additionally, the assessment process was tailored to the student's abilities based on the assessment outcomes. The school offered a diverse range of services to ensure that they could provide the best possible support for all students. In conclusion, in managing educational services, the principal and teachers strive to work cooperatively to plan, execute, and evaluate school-related activities effectively.